GambaranTingkat Keparahan Jaringan Periodontal pada Penderita Diabetes Melitus di Puskesmas Martapura Timur - Rasuna Ulfah; Wulandari Kai, Meggy; Habibah, Siti Sabatul; Amperawati, Metty (Poltekkes Kemenkes Banjarmasin, 2025)
Diabetes Mellitus (DM) is a chronic, non-communicable disease but is one of the global health challenges. The prevalence of Diabetes Mellitus in South Kalimantan has increased every year. This can be seen from the increase in the prevalence of Diabetes Mellitus in 2013 by 1.4% to 1.80% in 2018. Cases of Diabetes Mellitus in 2019 were at 67,783 cases, and in 2020 increased to 122,919 cases, with the number of cases in the Banjar Regency area being 5829 cases in 2022. This study aims to determine the description of the severity of periodontal tissue in patients with diabetes mellitus at the East Martapura Community Health Center, Banjar Regency, South Kalimantan. This type of research is descriptive research. The population in this study amounted to 30 people with a sampling technique using purposive sampling. The study found that 33.3% of diabetes mellitus patients experienced periodontal disease, with tartar deposits, 23.3% shallow pockets, and 43.3% deep pockets. The study concluded that the most common periodontal disease severity among diabetes mellitus patients at the East Martapura Community Health Center was deep pockets measuring 4-5 mm. It is recommended that individuals improve their oral hygiene practices to prevent further damage